Further Insights on Fake-Barn Cases and Intuition Variation. (19th March 2023) - Bergenholtz, Carsten; Busch, Jacob; Praëm, Sara Kier
Abstract: Studies in experimental philosophy claim to document intuition variation. Some studies focus on demographic group-variation; Colaço et al., for example, claim that age generates intuition variation regarding knowledge attribution in a fake-barn scenario. Other studies claim to show intuition variation when comparing the intuition of philosophers to that of non-philosophers. The main focus has been on documenting intuition variation rather than uncovering what underlying factor(s) may prompt such a phenomenon. We explore a number of suggested explanatory hypotheses put forth by Colaço et al., as well as an attempt to test Sosa's claim that intuition variance is a result of people 'filling in the details' of a thought experiment differently from one another. We show (i) that people respond consistently across conditions aimed at 'filling in the details' of thought experiments, (ii) that risk attitude does not seem relevant to knowledge ascription, (iii) that people's knowledge ascriptions do not vary due to views about defeasibility of knowledge. Yet, (iv) we find no grounds to reject that a large proportion of people appear to adhere to so-called subjectivism about knowledge, which may explain why they generally have intuitions about the fake-barn scenario that vary from those of philosophers.